2001
DOI: 10.4049/jimmunol.167.7.3887
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Trefoil Factor Induces Decay-Accelerating Factor Expression and Enhances the Protective Activities Against Complement Activation in Intestinal Epithelial Cells

Abstract: Mucosal damage induces a massive influx of serum complement components into the lumen. The epithelium produces a number of factors that can potentially ameliorate injury including intestinal trefoil factor (ITF), a small protease-resistant peptide produced and secreted onto the mucosal surface by goblet cells, and decay-accelerating factor (DAF), a protein produced by columnar epithelium which protects the host tissue from autologous complement injury. However, coordination of these intrinsic defensive product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 45 publications
3
46
1
1
Order By: Relevance
“…Peptidoglycan motifs that are recognized by NOD1 are delivered into host cells via the cag secretion system, and an important signaling event mediated by NOD1 is activation of NF-B (24). However, although other investigators have shown that DAF regulation is responsive to NF-B activation by pro-inflammatory stimuli (43,50), our data demonstrate that NF-B activation is not necessary for DAF induction by H. pylori. Another intriguing hypothesis based on a recent investigation (51) is that binding of CagL to cell surface ␣ 5 ␤ 1 integrins can alter local membrane dynamics and eventuate in the assembly of focal adhesions that trigger integrin signaling cascades (52).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Peptidoglycan motifs that are recognized by NOD1 are delivered into host cells via the cag secretion system, and an important signaling event mediated by NOD1 is activation of NF-B (24). However, although other investigators have shown that DAF regulation is responsive to NF-B activation by pro-inflammatory stimuli (43,50), our data demonstrate that NF-B activation is not necessary for DAF induction by H. pylori. Another intriguing hypothesis based on a recent investigation (51) is that binding of CagL to cell surface ␣ 5 ␤ 1 integrins can alter local membrane dynamics and eventuate in the assembly of focal adhesions that trigger integrin signaling cascades (52).…”
Section: Discussioncontrasting
confidence: 46%
“…The daf promoter contains a B response element, and activation of NF-B leads to the up-regulation of DAF in response to proinflammatory stimuli (41)(42)(43)(44). To define the role of NF-B in H. pylori-induced DAF expression, MKN28 cells were transiently transfected with constructs that express either a dominant-negative IB␣ or dominant-negative IB kinase ␤ as well as a NF-B-responsive luciferase reporter construct.…”
Section: H Pylori Induction Of Daf Occurs Via a Nf-b-independentmentioning
confidence: 99%
“…At the same time, gut epithelial cells themselves can synthesize and secrete complement locally (34 -36). As indicated (see Introduction), evidence for the involvement of complement activation has been obtained in different forms of IBD as well as gastritis (19,37,38). In all of these diseases, C3b deposition can be detected on luminal epithelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…In humans, under constitutive conditions, DAF is expressed sporadically on the luminal surface but, as indicated (see Introduction), its expression is up-regulated during inflammation (16,38,40). Despite these and the above observations, the importance of intrinsic complement regulatory activity in the GI tract has received little study.…”
Section: Discussionmentioning
confidence: 94%
“…The representation of components of complement system during the course of mucosal damage has been described in several previous studies, [39][40][41][42] but it is still limited. In the present study, we provide evidence that complement…”
Section: Discussionmentioning
confidence: 99%